2003
DOI: 10.1097/00004836-200305000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Reduction of the α-Fetoprotein Level After Lamivudine Treatment of Patients with Chronic Hepatitis B Virus Infection and Cirrhosis

Abstract: Markedly elevated alpha-fetoprotein levels in the range of >1,000 ng/mL are highly suspicious for the presence of hepatocellular carcinoma. This report describes three patients with cirrhosis and replicating hepatitis B virus infection who presented with initial serum alpha-fetoprotein levels of >1,000 ng/mL without clear evidence of hepatocellular carcinoma based on multiple abdominal imaging studies. Initiation of lamivudine treatment led to rapid and dramatic reductions in the alpha-fetoprotein level to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…2). Previous reports have documented a decrease in AFP in patients with chronic hepatitis B during lamivudine treatment [31] and case reports have documented a similar pattern of AFP improvement during antiviral therapy of hepatitis C [32]. In this study, the average decrease in AFP levels between baseline and 20 weeks of treatment was approximately 40%.…”
Section: Percent Change In Afpsupporting
confidence: 69%
“…2). Previous reports have documented a decrease in AFP in patients with chronic hepatitis B during lamivudine treatment [31] and case reports have documented a similar pattern of AFP improvement during antiviral therapy of hepatitis C [32]. In this study, the average decrease in AFP levels between baseline and 20 weeks of treatment was approximately 40%.…”
Section: Percent Change In Afpsupporting
confidence: 69%
“…Longitudinal studies showed that elevations of serum AFP levels at baseline in CHB patients confirmed by liver biopsy had been proven to be associated with a higher risk of decompensated cirrhosis, hepatocellular carcinoma (HCC), 16,17 implying that patients with elevated serum AFP had more advanced liver disease than did those with normal levels. Very high levels of serum AFP suggestive of the possibility of HCC were occasionally found in patients with chronic HBV infection, especially those with cirrhosis, but no occurrence of HCC 18,19 . In the setting of chronic hepatitis C, the mean serum AFP value was significantly greater in patients with more marked fibrosis 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have documented a decrease in AFP in patients with chronic hepatitis B during lamivudine treatment [17] and case reports have documented a similar pattern of AFP improvement during antiviral therapy of hepatitis C [18].…”
Section: Discussionmentioning
confidence: 85%